KEDISIPLINAN KERJA PEGAWAI PADA KANTOR PERTANAHAN KOTA PONTIANAK - Rizal, Maulana Filani; Mursalin, Adi; Wibowo W, Irvan; Rawa, Ricola Dewi; Hendarsa, Angga (Jurnal Ekonomi Integra, 2025)
This study aims to determine how the employee's work discipline in the pontianak city land office. The research method that the author uses in this study is the survey method while the data analysis method uses average analysis. The population in this study were 45 municipal land office employees in Pontianak. In this study using a non probability sample that is total sampling / saturated sampling as a sampling technique, this technique takes the same sample with a total population of 45 employees. Based on the analysis the results obtained in the form of leadership often provide direction or guidance for employees, leadership assertiveness encourages discipline and conditions of human relations with leaders and coworkers encourage discipline which is equal to 4.71 with very good meaning because it is in the range of class intervals 4.51 - 4.71 and the lowest value is the sanction given is felt to be heavy with a value of 3.69 or with a very bad meaning because it is in the range of class intervals from 3.69 to 3.89. Overall based on the research respondents obtained an overall average of 4.41 so that the disciplinary work of employees in the land office in Pontianak City is good.